PENGARUH LAJU KOROSI DAN UMUR PAKAI PADA TANGKI BAJA DI PLTD NAMLEA KABUPATEN BURU - Erwin Patikayhattu; Herjuno Tri Narpati; Leslie S. Loppies; H. S. Latumaerissa; Sanny Hahury (Jurusan Teknik Mesin, 2025)
Storage tanks, also commonly referred to as storage tanks, are one of the units or pieces of equipment used to store fuel. One industry that uses this equipment is the Namlea PLTD located in Buru Regency. The type used is a Fixed Cone Roof Tank to accommodate fuel that will be supplied to the power plant engine (Diesel Engine). The service life of the tank is ± 5 years, but based on field observations, it appears that there is corrosion on the surface of the tank, which is quite fast. Concerning that, the purpose of this study is to calculate the corrosion rate and corrosion hazard during the general period of use. The method used in data collection is field observation by measuring plate thickness using an Ultrasonic Thickness Gauge. Furthermore, the measurement results were analyzed using the API 563 standard to calculate the corrosion rate. The results showed that the corrosion rate on the tank blanket (shell) at the first level was 0.9 mm/year, the second level was 0.6 mm/year, the third level was 0.88 mm/year, the fourth level was 0.9 mm/year, and the fifth level was 0.85 mm/year. Then the remaining life for shell parts at the first level is 6 years, the second level is 7.6 years, the third level is 7.8 years, the fourth level is 7.9 years, and the fifth level is 9 years. The results of data processing indicate that the 300 KL diesel tank remains feasible for operation in Namlea PLTD, Buru Regency. Keywords: Fixed Cone Roof Tank, standard, thickness, corrosion rate